Philosophy and Working-through the Past : a Psychoanalytic Approach to Social Pathologies. - Jackson, Jeffrey M. (Lexington Books, 2013)
Philosophy and Working-through the Past defends the relevance to philosophy of the implications of Freud's conception of object loss, especially his provocative discussions of mourning and melancholia. It engages with ongoing debates concerning the relevance of psychoanalysis to social theory, and suggests that emancipation from pathological culture be conceived as a mournful process of working-through the past.